2007
DOI: 10.1016/j.coi.2007.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Testing the organization of the immunological synapse

Abstract: Upon encounter with antigen-bearing presenting cells, T cells initiate the formation of a unique junction termed the immunological synapse (IS). The morphology of this junction, characterized in EM as a series of discrete contacts into which are interspersed synaptic spaces [1], has multiple similarities to neuronal synapses. The closely apposed membranes permit engagement of T cell receptors (TCR) on T cells with peptide-major histocompatibility complexes (pMHC) as well as distinct contacts for other receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…However, although these studies can provide a useful foundation for investigation of the mechanisms of B cell activation, a molecular dissection necessitates the characterization of pathways and interactions within their correct cellular context (Krummel, 2007;Treanor and Batista, 2007). Such dissections have been made feasible through recent advances that allow for the spatiotemporal dynamics of particular molecules to be monitored within cells in real time.…”
Section: Introductionmentioning
confidence: 99%
“…However, although these studies can provide a useful foundation for investigation of the mechanisms of B cell activation, a molecular dissection necessitates the characterization of pathways and interactions within their correct cellular context (Krummel, 2007;Treanor and Batista, 2007). Such dissections have been made feasible through recent advances that allow for the spatiotemporal dynamics of particular molecules to be monitored within cells in real time.…”
Section: Introductionmentioning
confidence: 99%
“…T cells are activated by the presentation of antigen by professional antigen‐presenting cells. This process involves morphological rearrangements including the formation of a structure at the interface between the two cells referred to as the immunological synapse 5 . In vivo imaging of T‐cell activation has revealed that T cells can remain in contact with antigen‐presenting cells for hours, 6 and can still interact at the point of cell division more than 20 h after activation 7 , 8 .…”
Section: Resultsmentioning
confidence: 99%
“…This process involves morphological rearrangements including the formation of a structure at the interface between the two cells referred to as the immunological synapse. 5 In vivo imaging of T-cell activation has revealed that T cells can remain in contact with antigen-presenting cells for hours, 6 and can still interact at the point of cell division more than 20 h after activation. 7,8 With recent observations that T cells can undergo asymmetric cell division to dictate cell fate, 9 there is strong incentive to develop new approaches to in vitro imaging of T-cell interactions with dendritic cells over hours and even days.…”
mentioning
confidence: 99%